Adolescer em um contexto fundamentalista pentecostal gaúcho - Lirio, Luciano de Carvalho (2013)
This research was carried out with the support of CAPES Brasil and proposes a reflection on the adolescence experienced in a Gaúcho Pentecostal fundamentalist context , adopting as parameter the Igreja Batista Conservadora [The Conservative Baptist Church], having as a specific goal to conceptualize what it means to be adolescent in these churches which arise in a neo-Pentecostal, postmodern and pluralist religious Brazilian scenario, but which evoke a belonging to the classical Pentecostal movement begun in the country a century ago. In the first chapter I propose the analysis of the adolescence experienced in fundamentalist religious spaces, and being more specific, in a denomination which was born in Rio Grande do Sul. Observing which cultural manifestations are produced in this scenario, I use as theoretical-methodological references the contributions from Psychology, Sociology, Biological Sciences and their articulation with Theology and Pedagogy in the postmodern perspective. The second chapter proposes a reflection on fundamentalism and its influence on Gaúcho Pentecostal adolescents, having as a specific goal to analyze how the adolescents construct and share particular ways of understanding the globalized world, understand the reality which is drawn out around them and express the faith in a fundamentalist Gaúcho context. In the third chapter the fundamentalism is analyzed in a Christian Protestant Pentecostal cutout, recognizing that other fundamentalist matrices exist and thus delimiting the perimeter of the research. A social research was carried out so as to verify the reality experienced by the adolescents in a Gaúcho Pentecostal fundamentalist context.